Case reportDisseminated atypical molluscum contagiosum as a presenting symptom of HIV infection - Filo-Rogulska, Marta; Pindycka-Piaszczyńska, Malgorzata; Januszewski, Krzysztof; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Atypical forms of molluscum contagiosum may be challenging to diagnose and are found in immunocompromised patients where they indicate severe impairment of cellular immunity. We report a case of disseminated atypical molluscum contagiosum which was the first sign of HIV infection and AIDS disease in a 38-year-old male patient. The lesions – painless, flesh-colored and violaceous papules and nodules – spread systematically for previous 3 years. They were located on the face, forearms, in the groins and in the genital region. Serologic tests for HIV-1 and hepatitis C virus were positive. CD4+ T–cells count was 80/mm3. The skin biopsy showed intracytoplasmic molluscum bodies. Atypical, recalcitrant, disseminated or facial molluscum contagiosum requires immediate HIV testing. In our patient, both the opportunity for early diagnosis and the institution of effective therapy were missed.